The Effect of Profitability, Liquidity, And Working Capital on Capital Structure in Manufacturing Companies Including Multiple Industrial Sectors and Consumer Goods Industry Sector Listed on The Exchange Indonesia Effect - Natalia Naibaho (TRIGIN PUBLISHER, 2021)
The capital structure of the company is one of the fundamental factors in the company's operations. Determination of the proportion of debt and equity in its use as a source of corporate funding is closely related to the term capital structure. This study was conducted to better understand whether there are and how big the variables profitability, liquidity and working capital affect capital structure in manufacturing companies covering various sectors of industrial and consumer goods industry sectors listed on the Stock Exchange during the period of study (2009- 2011). As described in previous studies sourced from journals and reference books that these variables affect the capital structure, so here the author tries to discuss again within different periods and different data. Sampling was done by purposive sampling method with the criteria listed in the Indonesia Stock Exchange and has complete financial statements. The study sample consists of 25 companies. Analysis using descriptive and statistical analysis (linear regression) using SPSS version 17.0. Partially, the results showed that the profitability and working capital significantly and negatively related to capital structure while the liquidity variable positive and significant impact on the capital structure of the company various industry sectors and consumer goods industry in Indonesia Stock Exchange. Simultaneously, the results showed that the variables of profitability, liquidity, and capital working together positive and significant impact on capital structure. Where the level of significance seen sig. which shows the rate < 0.05.